Penyebab Terjadinya Kerugian Finansial Pada Perusahaan - Nandini, Qadrina (Universitas Muhammadiyah Sumatera Utara, 2022)
In this study, it is intended to be able to understand what causes financial losses to the company and to understand how to run a company properly and correctly, and also know how to avoid financial losses to the company. We researched this article using the literature review that I have read in the article and also cases of losses in companies that occurred in Indonesia. The results of the research that we researched, there are still many companies that are careless in running their business so that they cause financial losses, there are also some business managers who still do not have a realistic attitude in managing their business. Therefore, the person who manages the business must first have a straightforward and realistic attitude, and who is good at managing cash finances in the company to avoid financial losses. The company will run well if it is carefully planned.